A case-series evaluation of the impact and processes of a service-learning programme on and for caregivers and their children with neurodevelopmental disabilities - Cooke, Nicole (Rhodes University, Faculty of Humanities, Department of Psychology, 2019)
This thesis presents a series of three case studies from data collected as part of a research project exploring the process and impact of a service-learning programme with caregivers and their children with neurodevelopmental disabilities. Following a descriptive case series design, both quantitative and qualitative data are presented to create a comprehensive and rich understanding of each case. In particular, the data tracks change processes in the subjective well-being of the caregiver, the quality of the caregiver-child relationship and the functional development of the child over a twenty-one-week period of receiving public health services and an eight-week period of adding the service-learning programme. The paper also presents qualitative data on the caregivers' perceptions of and experiences of the public services and the servicelearning programme that the caregivers and their children received. The findings provide important insight into the caregivers' perceptions of giving and receiving care, with the caregivers' experiencing significant levels of distress and prominent barriers to accessing healthcare that were seemingly eased with the addition of the service-learning programme. The findings also point to a notable disparity between the quantitative findings and the qualitative interviews with questions being raised about the research being viewed as an intervention in itself.
Keywords: Developmentally disabled children -- Care; Caregivers -- Training of; Service learning -- Case studies